ANALISIS FRAUD DIAMOND DALAM MENDETEKSI FINANCIAL STATEMENT FRAUD (STUDI EMPIRIS PADA PERUSAHAAN PROPERTIES DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015) - Jenar Zharif Trihono, 13.05.52.0143; Setyowati, Widhy (Students' Journal of Accounting and Banking, 2017)
This research objective is to analyze fraud diamond influence which is proxied by financial stability, external pressure, financial target, industry character, auditor change, directors change, toward fraudulent financial statement on properties and real estate companies registered in Bursa Efek Indonesia (BEI) during 2013-2015 period. The samples used are 47 properties and real estate companies .The sampling method is purposive sampling with research period during 2013 to 2015. Correlation and influence between the variables are explained by using multiple linear analysis method.Research result shows that financial stability does not effecting, external pressure and financial target effect is significant negative, nature of industy, change in auditor, directors change do not effecting toward fraudulent financial statement.Keywords: Fraud Diamond, Fraudulent Financial Statement, Financial Stability, External Pressure, Financial Target, Industry Character, Auditors Change, Directors Change